Studi Interaksi Obat Antidiabetes Metformin dan Glibenklamid dengan Jamu pada Tikus Diabetes yang Diinduksi Aloksan - Sundhani, Elza; Diniatik; Rahman Hakim, Zainur; Nurzijah, Ika; Prakoso, Ardiasa; Fajrina, Nur; Rifki, Muhamad; Arifin Misgi Candra Dasa, Zaenal (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
Jamu is widely used in Indonesia as a Complementary and Alternative Medicine to treat Diabetes Mellitus. Potential interactions of metformin and glibenclamide with Jamu can affect the effectiveness of the hypoglycemic activity. This study aimed to examine the interaction of metformin and glibenclamide combined with jamu A (Smallanthus sonchifolius) and jamu B (Andrographis paniculata (Burm. F), Boesenbergia pandurata Roxb, Phyllanthus niruri L, Syzigii polyanthi) in hypoglycemic activity on an alloxan-induced rat. TLC-Densitometer method was used for phytochemical screening of Jamu and ethanolic extract plants. Thirty male Wistar rats were divided into ten treatment groups with alloxan (175 mg/Kg BW) as the induction model for DM 2 rats. Blood glucose levels were measured on days 0,-7,-14,and-21. The chromatogram profile results showed that the comparison plants had the same Rf values ​​between jamu A and B. The combination of Metformin with Jamu A and B showed a decrease in hypoglycemic activity, which was thought to be due to the inhibitory activity of metformin absorption, which was not significant compared to the single treatment (p>0.05). The combination of glibenclamide with jamu A and B showed a significant decrease in hypoglycemic activity (p<0.05) compared to the single treatment. The effect of the active compounds in jamu in influencing the activity of CYP3A4 and CYP2C9 enzymes (glibenclamide metabolizing enzymes) or antagonistic effects is predicted to occur in this combination. More research is needed to establish the mechanism of this interaction; however, this study can consider the potential interaction between metformin and glibenclamide with antidiabetics jamu.